A tour of Reconstruction : travel letters of 1875 - Dickinson, Anna E. (Anna Elizabeth), 1842-1932 (New directions in southern history., 2011)
'A Tour of Reconstruction', punctuated with a wealth of historical observations and entertaining anecdotes, is the story of one woman's experiences in the postbellum South.